К проблеме антисемитизма в Азербайджане (Ադրբեջանում հակասեմականության հիմնախնդրի շուրջ) - Էլիբեգովա Անժելա (YSU Journal of International Affairs, 2015)
Having both historical and religious background, the problem of anti-Semitism and anti-Zionism in Azerbaijan officially is silenced and replaced by actively promoted thesis of tolerance and multiculturalism. However, the frequency of anti-Israeli speeches and anti-Semitism at domestic, social level reveals the existence of the problem in the country, the denial attempts of which reveal the hypercompensation – an attempt to hide the drawback at a domestic level, applying too much effort for persuasion of foreign audiences in its absolute absence.